2011
DOI: 10.3892/mmr.2011.641
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin protects human osteosarcoma cells from oxidative stress-induced apoptosis through mitochondrial-mediated signaling

Abstract: Abstract. Apoptosis of osteoblasts has been proposed as the common basis of osteoporosis, with oxidative stress as the major cause. This study was performed to investigate the protective effect of simvastatin (0.001-0.1 µM) on 100 µM hydrogen peroxide (H 2 O 2 )-mediated oxidative stress-induced apoptosis in human osteosarcoma (MG63) cells and the molecular mechanisms involved. Cell apoptosis was evaluated by observation of morphological changes and Annexin V-propidium iodide double staining followed by flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(37 reference statements)
0
5
1
Order By: Relevance
“…Indeed, ibandronate had just a minor effect on NADPH, which was significantly reduced by simvastatin in PC-3 and MDA-MB-231 cells ( Figure 2 A,B). Thus, we could not confirm a previous report indicating that simvastatin might protect MG-63 osteosarcoma cells from oxidative stress [ 59 ], which could be a result of an induction of the anti-apoptotic BCL2 apoptosis regulator by the runt related transcription factor 2 (RUNX2) in response to the treatment with hydrogen peroxide in that study [ 60 ]. As both genes had about the same basal expressions in the cell lines that were investigated in this study and were not significantly regulated, it rather appears possible that reduction of NADPH is a general sign for reduced energy metabolism in treated cells, also because data on the influence of simvastatin and ibandronate on the production of reactive oxygen species (ROS) appear contradictory ( Supplementary Table S2 showing respective literature citations).…”
Section: Discussioncontrasting
confidence: 93%
“…Indeed, ibandronate had just a minor effect on NADPH, which was significantly reduced by simvastatin in PC-3 and MDA-MB-231 cells ( Figure 2 A,B). Thus, we could not confirm a previous report indicating that simvastatin might protect MG-63 osteosarcoma cells from oxidative stress [ 59 ], which could be a result of an induction of the anti-apoptotic BCL2 apoptosis regulator by the runt related transcription factor 2 (RUNX2) in response to the treatment with hydrogen peroxide in that study [ 60 ]. As both genes had about the same basal expressions in the cell lines that were investigated in this study and were not significantly regulated, it rather appears possible that reduction of NADPH is a general sign for reduced energy metabolism in treated cells, also because data on the influence of simvastatin and ibandronate on the production of reactive oxygen species (ROS) appear contradictory ( Supplementary Table S2 showing respective literature citations).…”
Section: Discussioncontrasting
confidence: 93%
“…Several reports found that statins reduce levels of the anti-apoptotic protein Bcl2, and increase apoptosis and cell death [48][49][50] . Though, there is evidence that statins increase Bcl2 abundance which would desirable and in some instances reduce apoptosis and cell death [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that simvastatin exhibited an important neuroprotective role against I/R injury-induced neuronal apoptosis via suppression neuronal apoptosis and attenuation of neurological dysfunctions. Zhao et al ( 42 ) demonstrated that simvastatin protects human osteosarcoma cells from oxidative stress-induced apoptosis by downregulating caspase-3 and caspase-9 activation, as well as upregulating of Bcl-2 expression. Suppression of MMP-9 expression was also reported to reduce neuronal apoptosis following I/R injury ( 43 ).…”
Section: Discussionmentioning
confidence: 99%